Akurasi Arah Kiblat Berbasis Google Maps dan Global Positioning System Smartphone: Kajian Ilmu Falak terhadap Praktik Penentuan Kiblat Masyarakat Urban - Andy Litehua (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2026)
The advancement of digital technology has given rise to a new tendency among urban communities in determining the Qibla direction, namely through Google Maps and the Global Positioning System compass feature on smartphones. This article aims to examine the accuracy level of this method compared to the classical hisab method based on spherical trigonometry used in the science of falak. This research employs a Systematic Literature Review (SLR) approach following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, comprising the identification, screening, eligibility, and included stages, to ensure a transparent and replicable literature selection process. The search was conducted across Google Scholar, Garuda, Moraref, and Scopus databases, yielding 86 initial records that were screened down to 21 articles meeting the inclusion criteria for thematic analysis and synthesis. The study results indicate that Google Maps essentially calculates direction based on the great circle formula, which is in principle consistent with the Qibla azimuth in falak science. However, its field accuracy is influenced by several technical factors, namely magnetometer sensor calibration, local magnetic field interference, Global Positioning System receiver precision, and user device placement errors. The tolerance for Qibla deviation due to minor angular errors is generally still acceptable under fiqh, but the combination of several error sources may result in significant deviation if not re-verified using the rashdul Qibla method or conventional falak measuring instruments. This research recommends the use of digital applications as a preliminary tool rather than a sole method, which needs to be combined with astronomical verification to ensure the validity of the Qibla direction of places of worship.